2014
DOI: 10.1007/s40261-014-0233-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Irritable Bowel Syndrome (IBS), Assessed Using the IBS–Quality of Life (IBS-QOL) Measure After 4 and 8 Weeks of Treatment with Mebeverine Hydrochloride or Pinaverium Bromide: Results of an International Prospective Observational Cohort Study in Poland, Egypt, Mexico and China

Abstract: Background and ObjectiveIrritable Bowel Syndrome (IBS) has a substantial impact on health-related quality of life (HR-QoL) but high-quality data pre- and post-treatment using the IBS–Quality of Life (IBS-QOL) measure are limited. The objective of this study was to evaluate the changes from baseline of the IBS-QOL scores, symptom scores and health economic data in IBS patients, after 4 and 8 weeks of treatment with mebeverine hydrochloride or pinaverium bromide.MethodsThis was a prospective observational cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 12 publications
2
22
0
6
Order By: Relevance
“…The IBS-QOL overall score was similar in Egypt, Mexico, and Poland, but higher in China, which may be due to the cultural background in different countries, e.g. race, food, beliefs, social milieu, and health-care system [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IBS-QOL overall score was similar in Egypt, Mexico, and Poland, but higher in China, which may be due to the cultural background in different countries, e.g. race, food, beliefs, social milieu, and health-care system [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent prospective observational cohort study showed that the treatment with mebeverine hydrochloride (or with pinaverium) improved the QOL [38].…”
Section: Mebeverine and Qol In Ibsmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a functional intestinal disorder characterised by chronic or recurrent symptoms which cannot be explained by the presence of structural, metabolic, or biochemical alterations [1]. IBS has a significant effect on the patient's quality of life [2], both personal and social, and represents an economic burden as a result of increased healthcare costs and absence from work [3,4].…”
Section: Introductionmentioning
confidence: 99%